1994
DOI: 10.1002/pros.2990240308
|View full text |Cite
|
Sign up to set email alerts
|

A more objective staging of advanced prostate cancer—routine recognition of malignant endocrine structures: The assessment of serum TPS, PSA, and NSE values

Abstract: Bone scans, serum tissue-specific polypeptide antigen (TPS), prostate specific antigen (PSA), and neuron-specific enolase (NSE) were assessed in a total of 80 hormonally treated prostate cancer patients. Thirty-nine patients were free of osseous lesions; in 8 subjects, 3 or fewer scintigraphic hot spots were found; in 29 patients, more than 3 bone lesions were recorded. In 3 patients, a partial contribution of endocrine cell cancer structures was found, while in one patient, a homogeneous small cell carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 19 publications
0
28
0
3
Order By: Relevance
“…However, their numbers increase in neoplastic growths, and their prevalence correlates with tumor size and progression to hormone-resistant states (4)(5)(6)(7)(8)(9), suggesting that they may play a role in advancing the disease. A large number of clinical studies have shown that prostatic neuroendocrine-like cells and their associated markers serve as prognostic indicators of poor patient survival (10)(11)(12)(13)(14)(15)(16), providing further support for a functional link between neuroendocrine-like cells and tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…However, their numbers increase in neoplastic growths, and their prevalence correlates with tumor size and progression to hormone-resistant states (4)(5)(6)(7)(8)(9), suggesting that they may play a role in advancing the disease. A large number of clinical studies have shown that prostatic neuroendocrine-like cells and their associated markers serve as prognostic indicators of poor patient survival (10)(11)(12)(13)(14)(15)(16), providing further support for a functional link between neuroendocrine-like cells and tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of extensive multifocal NE features in tumors is an indication of increased aggressiveness and androgen independence (11)(12)(13). While the prognostic value of tumor NE status remains controversial, a strong link between NE status and long term, disease-specific survival has been reported (14).…”
mentioning
confidence: 99%
“…E . U | |W | f f i X | and hepatic or renal impairment (Tarle et al, 1994), the patients Si S3 S5 S7 Cl C3 C5 C7 were divided into two groups: one group (n = 8) with apparent non-50-T specific TPS increases during successful androgen ablation therapy 20 (TPS > 80 U ml-' in the S6-S8 observation period, testosterone T,' > T T T < 1 nmol 1-1 and PSA < 2 ng ml-'); and a larger group (n = 15)…”
Section: Resultsmentioning
confidence: 99%